Evaluation of high‐density lipoprotein‐bound long non‐coding RNAs in subjects with familial hypercholesterolaemia - Scicali, Roberto; Bosco, Giosiana; Scamporrino, Alessandra; Di Mauro, Stefania; Filippello, Agnese; Di Giacomo Barbagallo, Francesco; Spampinato, Salvatore; Pavanello, Chiara; Ossoli, Alice; Di Pino, Antonino; Calabresi, Laura; Purrello, Francesco; et al. (European journal of clinical investigation, 2024)
Background Long non‐coding RNAs (lncRNAs) could be attractive circulating biomarkers for cardiovascular risk stratification in subjects at high atherosclerotic cardiovascular disease risk such as familial hypercholesterolaemia (FH). Our aim was to investigate the presence of lncRNAs carried by high‐density lipoprotein (HDL) in FH subjects and to evaluate the associations of HDL‐lncRNAs with lipoproteins and mechanical vascular impairment assessed by pulse wave velocity (PWV). Methods This was a retrospective observational study involving 94 FH subjects on statin treatment. Biochemical assays, HDL purification, lncRNA and PWV analyses were performed in all subjects. Results LncRNA HIF1A‐AS2, LASER and LEXIS were transported by HDL; moreover, HDL‐lncRNA LEXIS was associated with Lp(a) plasma levels (p < .01). In a secondary analysis, the study population was stratified into two groups based on the Lp(a) median value. The high‐Lp(a) group exhibited a significant increase of PWV compared to the low‐Lp(a) group (9.23 ± .61 vs. 7.67 ± .56, p < .01). While HDL‐lncRNA HIF1A‐AS2 and LASER were similar in the two groups, the high‐Lp(a) group exhibited a significant downregulation of HDL‐lncRNA LEXIS compared to the low‐Lp(a) group (fold change −4.4, p < .0001). Finally, Lp(a) and HDL‐lncRNA LEXIS were associated with PWV (for Lp(a) p < .01; for HDL‐lncRNA LEXIS p < .05). Conclusions LncRNA HIF1A‐AS2, LASER and LEXIS were transported by HDL; moreover, significant relationships of HDL‐lncRNA LEXIS with Lp(a) levels and PWV were found. Our study suggests that HDL‐lncRNA LEXIS may be useful to better identify FH subjects with more pronounced vascular damage. Long non‐coding RNA (lncRNA) LEXIS was significantly expressed in high‐density lipoprotein (HDL) and it was associated with lipoprotein(a) [Lp(a)] plasma levels in familial hypercholesterolaemia subjects. In a secondary analysis, the study population was stratified into two groups based on the Lp(a) median value. The high‐Lp(a) group exhibited a significant downregulation of HDL‐lncRNA LEXIS compared to the low‐Lp(a) group. Finally, Lp(a) and HDL‐lncRNA LEXIS were significantly associated with the pulse wave velocity.